STUDY OF CALCIUM SULFATE SCALING INDEX TENDENCY CALCULATIONS AT DIFFERENT TEMPERATURE CONDITIONS IN INJECTION WATER SAMPLES FROM OILFIELDS - Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2007)
Calcium sulfate scale is a type of scale found in petroleum industry and shows seriousproblem, because it can plug pore media and cause a decrease in production rate.Actual calcium sulfate (CaSO4) concentrations of S1, S2, S3 and S4 injection watersamples were in the range of 0.0208 to 0.4583 meq/l. While, the values of solubility ofS1, S2, S3 and S4 water samples at 77,145 and 1770F are in a range of 23.20 to 27.43meq/l. Based on the results of calcium sulfate scaling tendency calculations showed thatthe values of solubility of S1, S2, S3 and S4 water samples at various temperature conditions(77,140 and 1750F) are higher than actual CaSO4 concentrations for the samewater samples. No occurrence of CaSO4 scale was found in all analyzed injection watersamples at different temperature conditions (77,140 and 1750F).